Forming new sex partnerships while overseas: findings from the third British National Survey of Sexual Attitudes & Lifestyles (Natsal-3). (6th June 2016) - Tanton, Clare; Johnson, Anne M; Macdowall, Wendy; Datta, Jessica; Clifton, Soazig; Field, Nigel; Mitchell, Kirstin R; Wellings, Kaye; Sonnenberg, Pam; Mercer, Catherine H
Abstract : Objectives: Travelling away from home presents opportunities for new sexual partnerships, which may be associated with sexually transmitted infection (STI) risk. We examined the prevalence of, and factors associated with, reporting new sexual partner(s) while overseas, and whether this differed by partners' region of residence. Methods: We analysed data from 12 530 men and women aged 16–74 years reporting ≥1 sexual partner(s) in the past 5 years in Britain's third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a probability survey undertaken 2010–2012. Results: 9.2% (95% CI 8.3% to 10.1%) of men and 5.3% (4.8% to 5.8%) of women reported new sexual partner(s) while overseas in the past 5 years. This was strongly associated with higher partner numbers and other sexual and health risk behaviours. Among those with new partners while overseas, 72% of men and 58% of women reported partner(s) who were not UK residents. Compared with those having only UK partners while abroad, these people were more likely to identify as 'White Other' or 'Non-White' (vs White British ethnicity), report higher partner numbers, new partners from outside the UK while in the UK and paying for sex (men only) all in the past 5 years. There was no difference in reporting STI diagnosis/es during this time period. Conclusions: Reporting new partners while overseas was associated with a range of sexual risk behaviours. Advice on sexual health should be included as part of holistic health advice for all travellers, regardless of age, destination or reason for travel.